BIBLE TRANSLATION – A LIGHTHOUSE AND A LIBRARY FOR THE PROMOTION AND PRESERVATION OF LANGUAGE AND ‘LITERATURE’ IN AFRICA: THE EXAMPLE OF CHINYANJA - Wendland, Ernst R. (Scriptura, 2004)
In this article I explore several implications of the thematic metaphorical terms "lighthouse" and "library" with reference to three translations of the complete Scriptures that have been made in the Chinyanja language of Malawi, Zambia, and Mozambique. How did these translations, one begun over a century ago, serve both to promote (enlighten, show the way, reveal the rocks) and also to preserve (act as a reservoir and repository for) the language and culture of the Chinyanja-speaking peoples of this south-central African region? My survey describes some of the major challenges, difficulties, and setbacks encountered along the way in contrast to certain outstanding successes that were achieved and new initiatives undertaken during this long history, which continues to be written in the new millennium. Several linguistic aspects of this progressive development are briefly examined in a comparative manner with reference to a number of Scripture passages as they appear in the most literal and most idiomatic Chinyanja versions. I conclude by summarizing the potential of mother-tongue Bible translation for enlarging, by way of preservation and promotion, the overall communication resources of any given language-culture, especially one that does not have a great corpus of published literature.